Some features of diversity and distribution of the charales species in Ukraine [Articol] - Borysova, Elena (CEP USM, 2014)
The species composition of Ukrainian charophytes is given on the basis of summarized published and original data. At present, there are 41 species from 6 genera known in the flora of Ukraine, namely: Chara L. (25), Nitella C. Agardh (9), Tolypella (A. Braun) A. Braun (4), Lamprothamnium papulosum (Wallr.) J. Groves, Lychnothamnus barbatus (Meyen) Leonh., and Nitellopsis obtusa (Desv. in Loisel.) J. Groves. The distribution pattern of the Charales species is discussed.
Keywords: Charales; species diversity; distribution; Ukraine